Effects of follicular and luteal phase-based menstrual cycle resistance training on muscle strength and mass - Kissow, J.; Jacobsen, K. J.; Gunnarsson, T. P.; Jessen, S.; Hostrup, M. (Sports Medicine, 2022)
There is an increasing interest in female athletic performance—especially concerning the impact of the female menstrual cycle on training response. Indeed, fluctuations in female sex hormones, estrogen and progesterone, during the menstrual cycle regulate protein metabolism and recovery processes in skeletal muscle and may thus impactexercise training-related outcomes. Studies demonstrate that anaerobic capacity and muscle strength are greatest during the follicular phase of the menstrual cycle, when estrogen levels peak. In addition, studies indicate that resistance training conducted in the follicular phase of the menstrual cycle (follicular phase-based resistance training) may be superior to luteal phase-based training in terms of enhancing muscle strength and mass. This raises the possibility that the physiological capabilities of skeletal muscle to adapt to exercise training are dependent on the menstrual cycle and can be important for female athletes in optimizing their training. In this paper, we critically review the current state of the art concerning the impact of menstrual cycle phase-based resistance training and highlight why follicular phase-based resistance training possibly is superior to luteal phase-based training in enhancing resistance training outcomes. Finally, we identify directions for further research.